A new diploid butterwort species (Pinguicula, Lentibulariaceae) from Sardinia - Bacchetta, Gianluigi; Cannas, Marcello; Peruzzi, Lorenzo (Phytotaxa, 2014)
A new diploid species belonging to Pinguicula sect. Pinguicula is described from Sardinia, an island where no butterwort was previously reported from. The taxonomic relationship of P. sehuensis sp. nov. with other species is briefly discussed.